The impact of the integration of artificial intelligence on Software-as-a-service applications and industry - CHEN, LANG (2018)
The study’s objective is to understand how the integration of AI impacts Software-as–a-service (SaaS) applications and industry. With the development of cloud computing, more enterprises moved their products and services from independent deployment to cloud platforms to reduce time and investment in the deployment and maintenance. As a result of it, the fast growth of SaaS market is approaching saturation and infusing artificial intelligence (AI) into SaaS applications innovation is expected to trigger unprecedented innovation in SaaS industry and differentiate SaaS enterprises from their competitors. Indeed, many big players have announced their offerings that integrated AI and applied them in the market to carve out positions in the market, which indicates the potential room for leveraging AI across various segments of SaaS industry.